Grid-connected Micro-grid Power Supply and Distribution Transformer Capacity Optimization System Design in the Electricity Sales Environment. Issue 2 (April 2021) - Cheng, Zhuo; Zeng, Weidong; Shu, Zhou; Liao, Wei; Lin, Yuyi
Abstract: With the current gradual opening of our country's electricity sales market and the successive improvement of related policies for grid-connected micro-grids, grid-connected micro-grid power supplies and their distribution transformer capacity have received attention and development. Based on the good development of my country's electricity sales market environment, this paper designs the grid-connected microgrid power supply optimization system and its distribution and conversion capabilities to optimize the quality of electricity sales and optimize the grid configuration. In view of the fact that the operation of the microgrid system in my country's market environment is more flexible at this stage, after a long time simulation test, a simulation analysis of the operation status of the grid-connected microgrid is carried out. In the course of the experiment, the electricity price in the distribution point process and the real-time changes of the electricity purchase price in the market will be considered comprehensively, and the processing in the micro-electricity system based on its distribution transformer capacity optimization system and the load forecast result will be considered. This article uses a power grid project actually constructed in East China as an example to analyze the results of simulation calculations. Then the NSGA-II algorithm is used to solve the optimized model for the cost and benefit composition of the grid. The optimized configuration method of the optical storage microgrid proposed in this paper can ensure the reliable power supply of users' important loads during the off-grid operation of the microgrid, increase the installed capacity of distributed photovoltaics, and the configured energy storage system also allows enterprises to achieve low electricity prices. Purchase electric energy at any time and use it to supplement the load's demand for electric energy during peak electricity price periods, thereby increasing revenue. The experimental research results show that the design of the grid-connected microgrid power supply capacity optimization system under the electricity sales environment studied in this paper can effectively reduce the additional investment required by external loads and the capacity of optical storage and distribution transformers. Only then can the economic marketing profit of the microgrid be improved to a certain extent.